2012
DOI: 10.9753/icce.v33.structures.59
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Load on the Building Caused by Overtopping Waves

Abstract: Wide crested dike can reduce the kinetic energy of the overtopping wave and make the overtopping wave to flow back to the seaside. If a coastal town were built on or near a dike, the overtopping wave running on the dike crest generates the force which can affect the buildings located in its path. However, quantifying the hydrodynamic load on the building caused by overtopping waves is not straightforward because little empirical formulas are given in literature for this kind of configuration. Therefore, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Based on these findings it was stated that only a 80% of the maximum run-up Rh,max was effectively contributing to the impact force on the wall. Substituting Equation 12into Equation 11 yields in a coefficient of 0.32, which was very close to what was found earlier as C1 = 0.30 by adapting the momentum flux theory and using regular waves (Chen et al, 2012). Hence, this finding served as a largescale confirmation that the prediction of quasi-static force peaks F2 using 80% of the maximum run-up height was also valid for irregular waves.…”
Section: Prediction Of Quasi-static Impact Force F2supporting
confidence: 86%
See 3 more Smart Citations
“…Based on these findings it was stated that only a 80% of the maximum run-up Rh,max was effectively contributing to the impact force on the wall. Substituting Equation 12into Equation 11 yields in a coefficient of 0.32, which was very close to what was found earlier as C1 = 0.30 by adapting the momentum flux theory and using regular waves (Chen et al, 2012). Hence, this finding served as a largescale confirmation that the prediction of quasi-static force peaks F2 using 80% of the maximum run-up height was also valid for irregular waves.…”
Section: Prediction Of Quasi-static Impact Force F2supporting
confidence: 86%
“…Based on these findings 80% of the maximum run-up height was effectively contributing to the maximum quasi-static force F2 on the wall. The results coincided well with previous small-scale studies (Chen et al 2012). After deconstructing the process chain preceding an impact, using the physically most meaningful parameters to predict the impact force, evaluating on a range of existing approaches, and observing the scattered prediction results, it was concluded that the impact behavior is highly stochastic and statistical analysis would be more beneficial.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, it is important for designers and owners to recognize the key hazards (e.g., building damage) from the overtopping flow. Chen et al (2012 and Ramachandran et al (2012) reported their laboratory work of overtopping flow loads on vertical structures on a dike crest by physical models at different scales. Common findings of these works suggested that the observed force evolution shape of overtopping flow has a double-peak, which is similar to the "church-roof" time history of wave breaking impact force proposed by Oumeraci et al (1993) for deeper water wave impacts on caissons and composite structures.…”
Section: Introductionmentioning
confidence: 99%